Investment Efficiency Between Listed And Unlisted Firms, And Big 4 Audit Firms’ Effect: Evidence From Korea - Park, Sambock; Kim, Imhyeon; Kim, Wooyoung (Journal of Applied Business Research, 2017)
We examine the difference in investment efficiency between listed and unlisted firms and the effects of auditing by Big 4 audit firms on the investment efficiency of firms. Generally, listed firms are large in size, have a high level of stakeholders’ demands on the firm information, and show large ripple effects of managers’ decision making. Listed firms have a demand hypothesis that they are motivated to provide high quality accounting information and an opportunistic behavior hypothesis that they are more motivated to make opportunistic financial reporting to meet the expectations of capital markets compared to unlisted firms. Consistent with previous study (Chen, Hope, Li & Wang, 2011), this study measures investment efficiency using the investment forecasting model as a growth opportunity function. The results of the study, in the analysis of full samples, the listed firms have significantly higher investment efficiency than the unlisted ones. In the over-investment samples, it is found that the listed firms have higher investment efficiency. On the contrary, in the under-investment samples, indicate it is found that the unlisted firms have higher investment efficiency. Finally, it is found that listed firms audited by Big 4 audit firms have the higher investment efficiency. This study contributes to the literature on investment efficiency of listed and unlisted firms. Finally, it is expected that it will provide useful information on investment efficiency by expanding the scope of research and making the measurement of variables more precise.